DYNAMICAL ANALYSIS OF BANDA SEA CONCERNING WITH EL NINO, INDONESIAN THROUGH FLOW AND MONSOON BY USING SATELLITE DATA AND NUMERICAL MODEL - Bambang Sukresno; I W. Kasa (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science))
Banda sea is subjected to external force such as El Nino South Oscillation (ENSO), Indonesian Through Flow (ITF) andMonsoon. All of these component Combined with Current System, caused sea dynamic. This study aimed to get further knowledge aboutBanda sea dynamic. Based on this phenomenon , this study was conducted with an hypothesis that sea level anomaly (SLA) and seasufrace temperature (SST) will decrease during ENSO event. Also that SLA and SST will seasonally change concerning with Monsoon.The pattern of current in eastern of Banda sea will be seasonally different concerning with monsoon while in western of Banda sea isalmost constant according to ITFThis research carried out in Banda Sea within the rectangular region from 122.42 E to 131.47 E , Latitude 03.47 S to 07.65 S.in period of 1996 to 2006 consist of northwest monsoon, southeast monsoon, 1st transitional month in April and 2nd transitional monthin October. Spatial analysis used to analyze annual and seasonal distribution of SST and SLA from satellite dataset, also by comparisonbetween wind data, ITF pathway and numerical model. SST derived from NOAA / AVHRR satellite data by applying MCSST algorithm,SLA derived from Topex/ Poseidon and Jason-1 Satellite data by applying Inverse distance weighted interpolation, while numerical modelderived from barothropic model using Princeton ocean model.Sea level anomaly and sea surface temperature is decrease according to ENSO event, such as descrease of SLA and SST duringENSO event in 1997 , 2002 and 2004. Sea level anomaly and sea surface temperature is change according to Monsoon that reverse every6 (six) month. SST and SLA get maximum level during northwest monsoon in November to March and get Minimum during Southeastmonsoon in May to September. There are strong correlation coefficient between annual Sea level anomaly and annual Sea SurfaceTemperature with index value up to 0.817104. on the other side correlation coefficient between seasonal Sea level anomaly and SeasonalSea Surface Temperature is 0.576469. Based on Patern of current we found that Western part of Banda sea is strongly affected by ITFwhile eastern part of Banda sea is strongly affected by monsoon.